Pembelajaran nahwu melalui tugas kelompok berbasis video: menelisik pandangan mahasiswa kelas icp pba 2023 - Rohmah, Ziyadatur (Maliki Interdisciplinary Journal, 2025)
This study aims to explore the views of International Class Program (ICP) of 2023 in the Arabic Language Education Study Program on learning nahwu through video-based group assignments. This study was motivated by students' difficulties in understanding abstract nahwu material and monotonous learning methods. With a descriptive qualitative approach and case study design, researchers collected data through open questionnaires and in-depth interviews with 24 students. The results showed that the learning strategy with video-based group assignments was able to increase students' active participation, strengthen their understanding of nahwu concepts, and develop skills in digital media production. Students felt more motivated because they were directly involved as learning subjects, both in understanding and explaining the material. However, several challenges also emerged, such as limited devices, lack of technical experience, and low post-video interaction. Nevertheless, most students responded positively to this strategy and considered learning to be more interesting and meaningful. These findings indicate that video-based group assignments are a potential approach to be applied in nahwu learning in the digital era, and contribute to the development of more participatory, creative, and effective Arabic language teaching methods.